Marketing de contenido en la comunicación política de los candidatos presidencia-les del Ecuador en instagram 2021-2024. - Rocillo Alba, Luis Emilio (My University, 2021)
Political communication has been adapted to all media outlets, including social media. Instagram is no exception because it is one of the fastest growing networks in the world and in Ecuador. The objective of the research is to know the impact of content marketing related to political communication on Instagram of the four most voted presidential candidates in the 2021 elections in Ecuador. 569 publications were collected on which several study models were selected on the basis of a bibliographic review, thereby raising qualitative and quantitative variables: frequency of publication, types of content and level of engagement generated. Xavier Hervas is the candidate with the most shared publications, using mostly political content, followed by citizens and intimates, obtaining with these strategies the highest level of engagement within the study. It should be noted that Hervas is a candidate with no political trajectory who excelled in the election with a 4th place obtaining 15.68% of votes, something that had not happened in Ecuador 15 years ago. The results show that despite being a careerless politician he manages to create a large community on Instagram for his brand that ends up backing him up in the election. It means that content marketing has a direct impact on political communication in a positive way if it is possible to adapt to a correct communication plan.
La comunicación política se ha adaptado a todos los medios de comunicación, entre los cuales se encuentra las redes sociales. Instagram no es la excepción debido a que es una de las redes con mayor crecimiento a nivel mundial y en el Ecuador. El objetivo de la investigación es identificar la incidencia del marketing de contenido relacionado con la comunicación política en Instagram de los cuatro candidatos presidenciales más votados en las elecciones 2021 en Ecuador. Se recolectaron 569 publicaciones sobre la cual en base a una revisión bibliográfica se seleccionaron varios modelos de estudio y con ello planteamos variables cualitativas y cuantitativas: frecuencia de publicación, tipos de contenidos y nivel de engagement generado. Xavier Hervas es el candidato con más publicaciones compartidas, utilizando contenidos en su mayoría políticos, seguido de ciudadanos e íntimos, obteniendo con estas estrategias el nivel más alto de engagement dentro del estudio. Cabe destacar que Hervas es un candidato sin trayectoria política que sobresalió en las elecciones con un 4to lugar obteniendo el 15.68% de votos, algo que no había ocurrido en el Ecuador hace 15 años. Los resultados demuestran que pese a ser un político sin trayectoria consigue crear una gran comunidad en Instagram para su marca que termina respaldándolo en las elecciones. Quiere decir que el marketing de contenidos incide directamente con la comunicación política de manera positiva si se consigue adaptar a un plan comunicacional correcto.
Keywords: MARKETING DE CONTENIDO; COMUNICACIÓN POLÍTICA